What are service sector innovations and how do we measure them? - Krzysztof Szczygielski (Center for Social and Economic Research (CASE), 2011)
Services dominate all advanced economies but service innovations are still an underresearched topic. One of the reasons are definitional and measurement difficulties. The goal of the paper is to highlight those by reviewing recent literature and to assess the current state of knowledge and challenges. Theoretical approaches, empirical techniques and selected empirical results are discussed. Apparently the biggest challenge, at this point, is to create a unified conceptual framework, that would encompass both manufacturing ad services. Meeting this challenge will, however, be difficult, given the strong focus on manufacturing, both in the literature and in the way enterprise surveys are designed.
Keywords: O30; O33; L89; 330; innovation; services; manufacturing; Innovation; Messung; Dienstleistungssektor